Rising Against the Thieves. Anti-Corruption Campaigns in South-Eastern Europe - Milan, Chiara (PARTECIPAZIONE E CONFLITTO, 2018)
Since the 2010s, bottom-up anti-corruption mobilizations have broken out in different countries of south-eastern Europe. Bosnia-Herzegovina in 2014 and Macedonia in 2015 and 2016 were amongst the states in democratic and economic transition in which thousands of people took to the streets to express their discontent against a ruling class blamed for corruption. Although triggered by different events, these mobilizations present a number of similarities. Building on qualitative interviews and ethnographic observation of interactions on social media platforms, this article investigates the discursive strategies that movement organizers used to frame their claims and the protestors’ identity in both countries. The article explores the ways in which protest leaders in the two countries appropriated the topic of corruption "from below" to delegitimize the ruling class using similar motivational, identity and diagnostic frames, notwithstanding the protests being spurred by diverse events. Furthermore, it elucidates the similarities and differences among the prognostic frames, that is, the proposed solutions to the problem of political corruption.